IDEB em São Gonçalo-RJ: influência dos resultados na implementação de políticas educacionais para o ensino fundamental II - Novaes, Raphael Ribeiro (2025)
This dissertation was developed within the Graduate Program in Education: Formative Processes and Social Inequalities, in the research line Policies, Rights, and Inequalities. The general objective of this study is to understand external factors outside the school that affect IDEB performance in the final years of elementary education in the municipality of São Gonçalo. To this end, the following specific objectives were established: to reflect on the IDEB, clarifying the purposes of large-scale assessment, its parameters and metrics; to discuss the contributions and gaps of large-scale assessments for public education, considering the criticism of managerialism that permeates such evaluations; and to analyze the data from educational assessment indexes, as well as the documents that guide education in the municipality of São Gonçalo. Brazilian education has been the stage for intense transformations in recent decades, through public policies that introduce a managerial logic, prioritizing quantitative results to the detriment of complex educational processes. The IDEB is a notable example of such measures. The managerialism inherent to large-scale assessments often fails to grasp the multifaceted reality of municipalities such as São Gonçalo-RJ, where factors like violence and social inequalities directly affect school life and students' learning capacity. This limited perspective, by focusing solely on numbers, overlooks the complex local dynamics and the barriers that prevent full educational development. Thus, the study draws on Ball (2002, 2005) for insights into managerialism in education; Bonamino and Souza (2012) and Capocchi (2017) for perspectives on large-scale assessments; and Freire (1989, 2003, 2005) to support discussions on the need for student autonomy and critical literacy, along with other authors used to support the research. The methodology adopted was a bibliographic and documentary review, aiming to reconstruct the educational context in São Gonçalo and understand the indexes and results of municipal schools in lower secondary education (Ensino Fundamental II). To achieve this, news articles published on newspaper websites and official pages were analyzed, in addition to documents, laws, and data related to the municipality and national assessment systems. The study concludes that, despite investments in São Gonçalo, educational progress faces complex challenges, such as political appointments and the discrepancy between student promotion and actual learning. School violence exacerbates this gap, resulting in diplomas that do not reflect the expected knowledge. Thus, the work questions whether the IDEB is a sufficient parameter to measure the quality of Brazilian education, highlighting the urgency of in-depth and critical studies on large-scale assessment models and their impacts.